Mechanisms of injuries in world cup alpine skiing - Bere, T. T. (2013)
The International Ski Federation (FIS) Injury Surveillance System (ISS) has reported that during the five-month winter season, one in every three World Cup (WC) alpine skiers sustains an injury. Similar to recreational skiers, the most common problem in ski racers is knee injuries, and the most frequent specific diagnosis is a complete rupture of the anterior cruciate ligament (ACL). Our knowledge of injury mechanisms in alpine skiing is limited, particularly among competitive skiers. Video of real injury situations contain important information of what took place when the injury occurred. This information, in turn, can form the basis for injury prevention strategies. The main aim of this thesis was therefore to describe the mechanisms of injuries in WC alpine skiing, based on systematic analysis of video recordings.